THE STRATEGY OF IMPROVING AGRITOURISM SERVICE AT SETIYA AJI FLOWER FARM BY USING IPA-KANO APPROACH - Ganestyani, Indah Arum; Jamhari, Jamhari; Masyhuri, Masyhuri (Jurnal Aplikasi Manajemen, 2019)
Setiya Aji Flower Farm Agrotourism is a chrysanthemum flower farm agrotourism located in Jetis Village, Bandungan, Semarang regency, Central Java. This research aims to recommend improving attribute's performance to give maximum satisfaction to visitors. The variable used in agrotourism service is the five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy, consisting of 32 attributes in entirety. The research was conducted on October-November 2018. Interviews and observations were used to collect the data. There were 100 visitors used as samples in this research, selected through quota sampling. IPA and Kano analyses were used to give a recommendation. It results in the management prioritizing concentrate here and one dimensional category.